Validity and Psychometric Evaluation of the Chinese Version of the 5-Item WHO Well-Being Index - Fung, Sai-fu; Kong, Chris Yiu Wah; Liu, Yi-man; Huang, Qian; Xiong, Zike; Jiang, Zhiquan; Zhu, Fangfang; Chen, Zhenting; Sun, Kun; Zhao, Huiqin; Yu, Ping (Frontiers in Public Health, 2022)
Aims: This paper evaluates the psychometric properties of the Chinese version of the 5-item WHO Well-Being Index (WHO-5) in mainland China. Methods: Two cross-sectional studies with 1,414 participants from a university in China were conducted. The Chinese version of the WHO-5 was assessed to determine its internal consistency, concurrent validity, factorial validity, and construct validity. Results: The results indicate that the WHO-5 is unidimensional and has good internal consistency, with Cronbach’s a = 0.85 and 0.81 in Study 1 (n = 903) and Study 2 (n = 511), respectively. The findings also demonstrate that the WHO-5 has good concurrent validity with other well-established measures of well-being, self-efficacy, self-esteem, and mental well-being. The results of confirmatory factor analysis also suggest that the scale has a good model fit, with χ2 (10.988) / 4 = 2.747, SRMR = 0.019, CFI = 0.999, TLI = 0.998, and RMSEA = 0.044. Conclusions: This study provides empirical data demonstrating that the Chinese version of the WHO-5 has good psychometric properties. The scale can be a useful measure in epistemological studies and clinical research related to well-being in Chinese populations.